The ideological origins of the dirty war fascism, populism, and dictatorship in twentieth century Argentina - Finchelstein, Federico 1975- (Oxford University Press, 2014)
Finchelstein tells the history of modern Argentina as seen from the perspective of political violence and ideology. He focuses on the theory and practice of the fascist idea in Argentine political culture throughout the twentieth century. He analyses the connections between fascist theory and the Holocaust, anti-Semitism and the military junta's practices of torture and state violence (1976-1983), its networks of concentration camps and extermination